CORRECTIVE FEEDBACK AND THE DEVELOPMENT IN WRITING A PARAGRAPH AT THE SECOND SEMESTER STUDENTS OF MUHAMMADIYAH KOTABUMI UNIVERSITY - Rulik Setiani (Didascein : Journal of English Education, 2021)
Corrective feedback is the most common ways of written feedback that usually used by lecturer to correct the mistakes of the students' writing and improve students' language accuracy in their writing tasks. Giving correction can be done by orally or written. It will inform about the errors of thestudents' writing especially a paragraph by Direct or Indirecrt corrective feedback. Furthermore, it also can encourage the students to improve their writing paragraph. The aims of the research are to investigate the types of corrective feedback that the lecturer provided in students' writing a paragraph, to investigate the students' development in writing a paragraph after receiving corrective feedback, and to investigate the dominant of corrective feedback that the lecturer provided in students' writing. This research employed qualitative research that examined 10 students in second semester of Muhammadiyah Kotabumi University. The instrument used was students' writing a paragraph. The result of this research showed that lecturer used both direct and indirect corrective feedbacks. It found that direct corrective feedback is more dominant than indirect corrective feedback. Moreover, it was also found that there were some improvements in their second written text after corrective feedback was given. In addition, giving some corrective feedbacks on students' writing paragraph could develop students' writing ability and motivate them revise and do better in their writing. Keywords: corrective feedback, direct and indirect, paragraph writing